2002
DOI: 10.1111/j.1151-2916.2002.tb00381.x
|View full text |Cite
|
Sign up to set email alerts
|

Spark Plasma Sintering of Alumina

Abstract: A systematic study of various spark plasma sintering (SPS) parameters, namely temperature, holding time, heating rate, pressure, and pulse sequence, was conducted to investigate their effect on the densification, grain‐growth kinetics, hardness, and fracture toughness of a commercially available submicrometer‐sized Al2O3 powder. The obtained experimental data clearly show that the SPS process enhances both densification and grain growth. Thus, Al2O3 could be fully densified at a much lower temperature (1150°C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

26
392
3
13

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 761 publications
(434 citation statements)
references
References 21 publications
26
392
3
13
Order By: Relevance
“…As the sintering temperature increases (1300 to 1400) ºC, the alumina grain growth is greater, so that at 1400 ºC an average grain size 1.4 m is observed. This grain size is very small compared to that of monolithic alumina sintered by SPS at 1400 ºC reported elsewhere [32], which is 5.0 m. Therefore, the nanoparticles of the second phase to the aluminium titanate leads to an inhibitory effect in alumina grain growth.…”
Section: Resultsmentioning
confidence: 93%
“…As the sintering temperature increases (1300 to 1400) ºC, the alumina grain growth is greater, so that at 1400 ºC an average grain size 1.4 m is observed. This grain size is very small compared to that of monolithic alumina sintered by SPS at 1400 ºC reported elsewhere [32], which is 5.0 m. Therefore, the nanoparticles of the second phase to the aluminium titanate leads to an inhibitory effect in alumina grain growth.…”
Section: Resultsmentioning
confidence: 93%
“…The effect has been explained by rapid heating due to Joule heating at contacts points, the presence of plasma in pores separating powder particles, and the intrinsic contribution of the current to mass transport. [23][24][25][26] Vickers hardness measurements were made on polished sections of the MoSi 2 -NbSi 2 composite using a 5-kg load and 15-s dwell time. The calculated hardness value of the MoSi 2 -NbSi 2 composite was 1180 kg/mm 2 .…”
Section: Resultsmentioning
confidence: 99%
“…It was also shown that the sintering behavior and densification rate are strongly dependent on the reactivity of the starting powder on the basis of the results of some 20 PECS-treated different commercially available alumina powders: powders having larger specific surface areas sinter and yield homogenous microstructures more easily than do coarse-grained starting powders [28]. However, PECS studies on different cation doped α-alumina powders have been lacking.…”
Section: Methodsmentioning
confidence: 99%
“…PECS densification of Mg 2+ (0.1 mass%)-doped α-alumina powders obtained by the impregnation method was reported to be also effective in suppressing grain growth as in the case of conventional sintering techniques, showing that the average grain size of non-doped and Mg-doped samples sintered at 1250°C under 50 MPa was 1.0 m (for a normalized comparison, the reported size is divided by 1.56 [29]) and 0.58 m, respectively [28]. It was also shown that the sintering behavior and densification rate are strongly dependent on the reactivity of the starting powder on the basis of the results of some 20 PECS-treated different commercially available alumina powders: powders having larger specific surface areas sinter and yield homogenous microstructures more easily than do coarse-grained starting powders [28].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation